Interpretation of Nushuz in the Qur'an: Comparative Study of Tafsir al-Jami' Li Ahkam al-Qur'an and Tafsir al-Munir - Nugraha, Sandi; Zulaiha, Eni (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to explore the understanding of Imam al-Qurtuby and Wahbah al-Zuhaili in interpreting the verses of the Qur'an regarding nushuz, as well as studying its relevance in preventing domestic violence. The research method used is qualitative with a comparative approach between tafsir al-Jami' Li Ahkam al-Qur'an by Imam al-Qurtuby and tafsir al-Munir by Prof. Dr. Wahbah al-Zuhaili. The results of the research show that both of them provide views on the resolution of nushuz in accordance with the principles of Sharia, with an emphasis on avoiding domestic violence. Husbands are reminded not to use abusive words or do actions that can damage the wife's honor, and the importance of a wise solution without involving violence is emphasized. This research also relates the findings to the Law of the Republic of Indonesia No. 23 of 2004 about PDKRT, highlights the need for harmony between religious interpretation and applicable legal provisions. It is hoped that the results of this research can provide a holistic view in dealing with the problem of nushuz and encourage a solution that upholds the values of humanity and justice in the household context.